A feedback LMS adaptive algorithm for active vibration control - Gao Shouwei; Huang Quanzhen; Shao Yong; Jiang Enyu; Zhu Xiaojin (2010 8th World Congress on Intelligent Control and Automation, 2010)
The modal damping of flexible spacecraft accessories such as solar panels being small, and in case of disturbance, attitude adjustment, and rotation cases, the significant vibration will continue for a long time, which will seriously affect the stability of the system. It has become a research hot spot how to reduce or eliminate the structural vibration response effectively. It is needed to get the related signal of excitation signal in the widely focused feed forward FXLMS (filtered-X least mean square) control algorithm, so a feedback control algorithms is presented in this paper. This algorithm is to use the system error signal to obtain an estimate of the original vibration signal and use the estimated value as the reference signal adaptive filter. To verify the feasibility and superiority of the proposed algorithm, the piezoelectric smart flexible plate is used to construct the corresponding experimental platform to simulate the solar arrays. Both the simulation analysis using MATLAB and the experiment result on the platform indict that the new control algorithm is effective and feasible.